Religious Pluralism and Tolerance in Sibolga: Challenges and Solutions in a Multicultural Society - Prayetno, Nanda Sekti; Sari, Ira Novita (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
Sibolga is a coastal city in Indonesia characterized by high ethnic and religious diversity, shaped by a long history of trade, migration, and cultural exchange. This study aims to examine how religious pluralism is managed and the challenges of tolerance in a multicultural society. Using a qualitative method through literature review and interviews, the research identifies two main realities: the potential for harmony through values of mutual cooperation, deliberation, and the local motto “berbilang kaum, satu tujuan” (“many groups, one goal”), as well as vulnerabilities caused by issues of ethnicity and religion (SARA), radicalism, economic inequality, and the politicization of religion. The findings highlight four strategies for strengthening tolerance: multicultural education, structured interfaith dialogue, the role of local leaders as mediators, and the revitalization of cultural values. The novelty of this research lies in its emphasis on solutions grounded in the social practices of Sibolga’s community, making it an adaptive model with potential for replication in other multicultural regions of Indonesia.